Semantic fields of ideographic dictionaries in English and Uzbek - Sadikova Sevinch Alievna (Periodica Journal, 2024)
This study explores the concept of semantic fields within ideographic dictionaries, focusing on the English and Uzbek languages. It examines how meanings are organized and categorized in ideographic dictionaries, highlighting the differences and similarities between the two languages. The research emphasizes the importance of cultural context in defining semantic fields and how these dictionaries serve as valuable resources for language learners and translators. By analyzing specific examples from both languages, the study aims to illustrate the effectiveness of ideographic dictionaries in capturing nuanced meanings and facilitating cross-linguistic understanding
Keywords: ideographic dictionary; semantic field; lexicography